EFFECT OF THE THICKNESS OF ALLOY LINING ON SEALING PERFORMANCE OF REACTION PRESSURE VESSELS METAL C-RING - LI Gan; XIE LinJun; LI Zheng; ZHENG JinSong; LI WenJing; LI XingGen; SHEN MingXue (Jixie qiangdu)
Spring energized metal C-ring is an important basic component which is crucial to ensure the safety of nuclear power plant operation. The thickness of alloy lining which is one of the component part of metal C-ring will affect the sealing performance of C-ring. This article has built C-ring three-dimensional elastic-plastic finite element analysis model. Based on the reliability of the theoretical model which is verified by the experimental study,thickness of alloy lining on the mechanical behavior and sealing performance of C ring are discussed. The results show that under the same amount of compression,the thicker the alloy lining,the larger C ring stiffness slightly. But it has no obvious effect on the springback characteristic of C ring.When alloy lining thickness is small,the plastic strain value is higher which is adverse for the sealing performance. On the contrary,the greater thickness of alloy lining,the more uniform contact stress distribution,but too thick alloy lining can lead to sealing face wrinkles. So for millions of kilowatt nuclear reactor pressure vessel（ RPV） with a metal C ring,in order to ensure that metal C ring has good sealing performance,alloy lining thickness value of 0. 5-0. 7 mm should be recommended in the project,in order to ensure the sealing performance of C ring.